Ocular swabs on exhumed bodies: An alternative to the collection of "classical" tissue samples in forensic genetics. (January 2020) - Agostini, V.; Bailo, P.; Chiti, E.; Linarello, P.; Gentile, G.; Primignani, P.; Giriodi, M.; Piccinini, A.
Highlights: DNA extraction from eye swabs. STR typing from exhumed bodies. Sample collection from cadavers alternative strategy. Abstract: We present the results obtained on DNA extracted from ocular (scleral/corneal) swabs collected from exhumed bodies at different times of burial. To our knowledge, there are no publications in the scientific forensic literature dealing with sclera/cornea as a source of DNA in the forensic laboratory. The obtained results demonstrate that cornea/sclera swabbing might be a promising alternative to the sampling of other tissues for DNA extraction even in highly putrefied bodies.